Existing capacity to manage pharmaceuticals and related commodities in East Africa: an assessment with specific reference to antiretroviral therapy - Waako, Paul J.; Odoi-adome, Richard; Obua, Celestino; Owino, Erisa; Tumwikirize, Winnie; Ogwal-okeng, Jasper; Anokbonggo, Willy W.; Matowe, Lloyd; Aupont, Onesky (Human resources for health, 2009)
East African countries have in the recent past experienced a tremendous increase in the volume of antiretroviral drugs. Capacity to manage these medicines in the region remains limited. Makerere University, with technical assistance from the USAID supported Rational Pharmaceutical Management Plus (RPM Plus) Program of Management Sciences for Health (MSH) established a network of academic institutions to build capacity for pharmaceutical management in the East African region. The initiative includes institutions from Uganda, Tanzania, Kenya and Rwanda and aims to improve access to safe, effective and quality-assured medicines for the treatment of HIV/AIDS, TB and Malaria through spearheading in-country capacity. The initiative conducted a regional assessment to determine the existing capacity for the management of antiretroviral drugs and related commodities.
Keywords: Pharmaceuticals; East Africa; Antiretroviral therapy